ADDP: The Data Prefetching Protocol for Monitoring Capacity Misses - Srivastava, Swapnita; Singh, P. K. (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2025)
Prefetching is essential to minimizing the number of misses in cache and improving processor performance. Many prefetchers have been proposed, including simple but highly effective stream-based prefetchers and prefetchers that predict complex access patterns based on structures such as history buffers and bit vectors. However, many cache misses still occur in many applications. After analyzing the various techniques in Instruction and Data Prefetcher, several key features were extracted which impact system performance. Data prefetching is an essential technique used in all commercial processors. Data prefetchers aim at hiding the long data access latency. In this paper, we present the design of an Adaptive Delta-based Data Prefetching (ADDP) that employs four different tables organized in a hierarchical manner to address the diversity of access patterns. Firstly, the Entry Table is queue, which tracks recent cache fill. Secondly, the Predict Table which has trigger (Program Counter) PCs as tags. Thirdly, the (Address Difference Table) ADT which has target PCs as tags. Lastly, the Prefetch Table is divided into two parts, i.e., Prefetch Filter and the actual Prefetch Table. The Prefetch Filter table filters unnecessary prefetch accesses and the Prefetch Table is used to track other additional information for each prefetch. The ADDP has been implemented in a multicache-level prefetching system under the 3rd Data Prefetching Championship (DPC-3) framework.ADDP is an effective solution for data-intensive applications since it shows notable gains in cache hit rates and latency reduction. The simulation results show that ADDP outperforms the top three data prefetchers MLOP, SPP and BINGO by 5.312 %, 13.213 % and 10.549 %, respectively.